Financial skill and self-control affecting the saving behaviour of income earners in Thai municipalities - Petpairote, Wannuda (International Journal of Innovative Research and Scientific Studies, 2023)
The researcher aimed to examine the saving behaviour of income earners in Thai municipalities using a survey research method. The questionnaires were validated by experts, and data from 400 questionnaires were analysed using multiple regression analysis (including the mean and standard deviation). The results showed that most people had savings, which, if the savers had no main income, would be sufficient to sustain life for less than three months. Also, their incomes were mostly allocated for expenses, with the remainder deposited as savings. The proportion of savings per month was about 5–15%, and the overall purpose of saving money was to provide for old age or retirement. The main factor used to choose a form of savings was the rate of return. The savings trend is likely to continue in the future. The internet was a source of knowledge about saving plans, and most savings were in the form of money deposited with financial institutions. The researcher found that personal factors, such as income and occupation; financial skill factors, such as financial literacy, financial behaviour, and financial attitude; and self-control influenced the saving behaviour of income earners in Thai municipalities with a statistical significance of p-value at 0.01.